2021
DOI: 10.3390/brainsci11060696
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Neural Correlates of Human Emotions across Multiple Stimulus Presentation Paradigms

Abstract: Most electroencephalography (EEG)-based emotion recognition systems rely on a single stimulus to evoke emotions. These systems make use of videos, sounds, and images as stimuli. Few studies have been found for self-induced emotions. The question “if different stimulus presentation paradigms for same emotion, produce any subject and stimulus independent neural correlates” remains unanswered. Furthermore, we found that there are publicly available datasets that are used in a large number of studies targeting EEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The gamma band exhibited the highest classification performance, indicating its crucial role in capturing information related to emotion processing. 96 This finding is consistent with previous research that has associated gamma oscillations with visual cognition, emotion, attention, and memory. 97 , 98 The higher classification accuracy of the gamma band suggests its sensitivity to emotional stimuli and its potential as a neural marker of emotional states.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The gamma band exhibited the highest classification performance, indicating its crucial role in capturing information related to emotion processing. 96 This finding is consistent with previous research that has associated gamma oscillations with visual cognition, emotion, attention, and memory. 97 , 98 The higher classification accuracy of the gamma band suggests its sensitivity to emotional stimuli and its potential as a neural marker of emotional states.…”
Section: Discussionsupporting
confidence: 93%
“…The identification of the gamma band as a robust neural marker of emotion processing in green spaces opens up avenues for further investigation. 96 Future studies could explore the specific cognitive and affective processes associated with gamma oscillations during exposure to green spaces. Additionally, the role of other frequency bands, such as alpha and theta, in emotional experiences within green environments could be investigated to gain a more comprehensive understanding of the neural mechanisms at play.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha band activity has long been examined in psychophysiological research in the context of the orienting response to visual and acoustic stimuli (e.g., geometric figures and tones); however, oscillatory activity during emotional processing has been less widely investigated. Previous literature reviews assessing EEG oscillatory activity during picture perception focused on a small number of studies showing inconsistent findings, and concluded that the emotional effects on alpha band activity were unclear (Güntekin et al, 2017; Güntekin & Başar, 2014; Masood & Farooq, 2021). Recently, systematic research has been conducted, and the studies reviewed here indicate that alpha desynchronization (ERD) over posterior sensors is reliably enhanced when viewing emotional compared with neutral pictures.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is called "Negative bias" and appears to be pervasive, as evidence has been found in a number of domains (Baumeister et al, 2001;Hilgard et al, 2014). While no conclusive evidence was reported in previous reviews of alpha activity (Başar & Güntekin, 2012;Güntekin & Başar, 2014;Masood & Farooq, 2021), a large and consistent body of evidence has demonstrated that emotional engagement modulates both cortical and autonomic responses, and this modulation is primarily driven by motivational intensity (or arousal) induced by visual stimuli, regardless of hedonic content (i.e., similar reactivity for unpleasant and pleasant, compared with neutral, stimuli; Adolphs & Anderson, 2018;Bradley et al, 2001Bradley et al, , 2012Codispoti & De Cesarei, 2007;Keil et al, 2008;Sabatinelli et al, 2005;Schupp et al, 2006;Zald, 2003). Therefore, one focus of the present review will be the valence-specificity of alpha emotional modulation, i.e., whether alpha activity is modulated only by unpleasant stimuli or also by those that are pleasant and whether the modulation is more pronounced for unpleasant, compared with pleasant, stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation